KONSENTRASI, DISTRIBUSI DAN KORELASI LOGAM BERAT Pb, Cr DAN Zn PADA AIR DAN SEDIMEN DI PERAIRAN SUNGAI SIAK SEKITAR DERMAGA PT. INDAH KIAT PULP AND PAPER PERAWANG – PROPINSI RIAU - Wulan, Sri Purnama; Amin, Bintal (Jurnal Kajian Lingkungan, 2013)
Research about heavy metal concentration and organic matters in waters and sediments inSiak River Near the harbor of Indah Kiat Pulp and Paper corporation were conducted onJuly 2012. Samples of water and sediment were collected from seven different station andanalyzed in the Integrated laboratory of Fisferies and Marine Science Faculty University ofRiau. The results of the average concentration of Pb, Cr, and Zn in Waters were 0,577 mg/L,0,099 mg/L, and 0,065 mg/L and 14,160 μg/g, 4,116 μg/g, and 3,867 μg/g in sediment. Theresults of simple liear regression between metal concentration of Pb, Cr and Zn and organicmatters in waters and sediments showed a positive correlation except for Cr in watersshowed a negative correlation. This means that increasing concentration Heavy metals inwaters and organic matters would be follow by the increasing of heavy metals concentrationin sediments. The concentration of all hevy metals in all stasion were below the standardconcentration of ERM and ERL also the PLI, Igeo and MPI.